2016
DOI: 10.1158/1078-0432.ccr-14-3382
|View full text |Cite|
|
Sign up to set email alerts
|

IL1 Receptor Antagonist Inhibits Pancreatic Cancer Growth by Abrogating NF-κB Activation

Abstract: Purpose: Constitutive NF-kB activation is identified in about 70% of pancreatic ductal adenocarcinoma (PDAC) cases and is required for oncogenic KRAS-induced PDAC development in mouse models. We sought to determine whether targeting IL-1a pathway would inhibit NF-kB activity and thus suppress PDAC cell growth.Experimental Design: We determined whether anakinra, a human IL-1 receptor (rhIL-1R) antagonist, inhibited NF-kB activation. Assays for cell proliferation, migration, and invasion were performed with rhIL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 28 publications
5
67
0
Order By: Relevance
“…We recently reported that inhibition of the NF-κB upstream inducer, IL-1α, using a clinically available antagonist (anakinra) suppressed pancreatic cancer in vitro and in vivo [27]. In this study, we focused on nafamostat mesilate, an anti-inflammatory drug used to treat pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that inhibition of the NF-κB upstream inducer, IL-1α, using a clinically available antagonist (anakinra) suppressed pancreatic cancer in vitro and in vivo [27]. In this study, we focused on nafamostat mesilate, an anti-inflammatory drug used to treat pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that several conventional cancer chemotherapeutic agents that activate NF-κB/p65 lead to unfavorable clinical outcome [27,32,33], and the DNA-binding ability of NF-κB/ p65 has been proposed as a major mechanism contributing to chemoresistance in CRC [9,22,34]. The naturally occurring compound thymoquinone could abrogate oxaliplatin-induced activation of NF-κB/p65 and enhance sensitivity to oxaliplatin in pancreatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1-mediated tumor promotion has been identified in different murine and human tumor types, including sarcomas, melanoma, pancreatic ductal adenocarcinoma (Ling et al, 2012;Melisi et al, 2009;Tjomsland et al, 2013;Zhuang et al, 2016), myelomas (Lust et al, 2016), and breast carcinomas and involves different mechanisms ( Figure 4A). IL-1 has been shown to sustain the expansion and immunosuppressive function of myeloid cells in tumor-bearing mice (Elkabets et al, 2010;Kaplanov et al, 2019;Pan et al, 2017).…”
Section: Il-1 Family Members In Cancer Progressionmentioning
confidence: 99%
“…Data from mouse models of PC showed that NF-kB is required for oncogenic K-Ras-induced tumor development. Treatments with Gemcitabine alone or in combination with IL-1 inhibitors decreased IL-1α-induced NF-kB activity, and reduced PC growth [29].…”
Section: Leptin-notch Crosstalkmentioning
confidence: 96%